Analysing Methods of Measuring the Level of Development Based on the Experimental Data - Farzad Karimi; Mostafa Ahmadvand; Ali Heidari (تحقیقات کاربردی علوم جغرافیایی)
This study aims at identifying optimal method for masuring degree and level of development with resprct to models commonly used (Taxonomy, TOPSIS, Moris, SAW, and VIKOR). It is an applied rsearch in terms of the purpose and also is a quantitative research that was carried out in a survey method. Statistical population of the study was the villages in the county with 20 or more households (89 villages). Accordingly, 566 rural households were determined and selected as a sample using Lin sample size table. To collect the data, a questionnaire was used. For determining the content validity of the questionnaire, a factor analysis and for internal consistency reliability, Cronbach's alpha was used. The Cronbach's alpha coefficient (0.561-0.955) indicated the optimality of the questionnaire. Matlab 7.10, Excel2010, SPSS20, and Arc-GIS Softwares were used for modeling the level of rural development in the county. Findings revealed that there was high significant relationship between the methods with regard to their ranking scores. Findings showed that the VIKOR was a suitable and powerful approach to determine level of rural development in the county. In VIKOR, the range of development degree was very high with compaire to other methods. In VIKOR similar to TOPSIS, negative and positive ideals were considered. VIKOR has a differenc with TOPSIS in considering criteria weight, In VIKOR at first, distance of each criterion from ideal was calculated, then the weights were added them. Therfore, in VIKOR against SAW and TOPSIS has a high sensivity to the weights. Furtermore, findings showed that Sarabtaveh, Deh Bare- Aftab Olia, and Tangary with regard to 51 criteria by 0.635, 0.608, and 0.579 scores, respectively were developing villages and Gavbarg, Cheshmeh Tabarghoo, Tal-Gahi with 0.182, 0.201, and 0.233 scores respectively were non-developed villages. Also, there wasn’t any village in level of completely undeveloped, developed and completely developed. Also, approximately half of villages (46.1 percent) with 21.46 percent of the population of the rural region were undeveloped villages. In addition, 69.35 percent of population in villages of the study was in developing stage.